Evaluation of the UK D.A.R.E. Primary programme - Evans, Emily; Tseloni, Andromachi (2018)
Aims: Results from the first evaluation of the UK Drug Abuse Resistance Education (D.A.R.E.) Primary programme, designed and undertaken by the (independent academic) authors on data collected in late 2015/early 2016 by the UK providers of the programme are presented. The evaluation assessed the programme against its learning outcomes (covering topics including pupils’ ability to communicate and listen, handle relationships and stress, make safe choices, get help from others) as well as their knowledge and use of substances.